Determinants of Loan Loss Provisioning and Their Effects In UK Commercial Banking System: An Empirical Study of Post Crisis Times - Rana, Raffay Ahmed (2015)
The study has examined UK’s banking system, looking particularly at the legislation, structure and regulatory bodies that govern and make policies about the banking system which is repeatedly exposed to various crises experienced in recent times. The purpose of the study is to determine the factors that impact the loan loss provisions in UK commercial banks over the sample period of 2009 – 2014. In the first stage, IV instruments are used to determine whether Z-score is exogenous or endogenous. In the second stage, Generalised Method of Moments (GMM) estimator is adopted to analyse the econometric model. The empirical results show the presence of pro-cyclicality in UK banking sector. The model shows no evidence for capital management and income smoothing behaviours for the chosen banks.